2019
DOI: 10.3847/1538-4357/ab3a94
|View full text |Cite
|
Sign up to set email alerts
|

A Weak Coronal Heating Event Associated with Periodic Particle Acceleration Episodes

Abstract: Weak heating events are frequent and ubiquitous in solar corona. They derive their energy from the local magnetic field and form a major source of local heating, signatures of which are seen in EUV and X-ray bands. Their radio emission arise from various plasma instabilities that lead to coherent radiation, making even a weak flare appear very bright. The radio observations hence probe non-equilibrium dynamics providing complementary information on plasma evolution. However, a robust study of radio emission fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 81 publications
4
21
0
Order By: Relevance
“…The energy variation in the system also follows a similar trend. This is exactly what was observed by Mohan et al (2019a). Based on this additional evidence, I present a physical model below.…”
Section: Physical Model Of Winqsessupporting
confidence: 78%
See 2 more Smart Citations
“…The energy variation in the system also follows a similar trend. This is exactly what was observed by Mohan et al (2019a). Based on this additional evidence, I present a physical model below.…”
Section: Physical Model Of Winqsessupporting
confidence: 78%
“…Recent simulations also hint towards a relationship between the two phenomena. Chen et al (2021) found three magnetic field orientations which can produce campfires and one of them match almost exactly with the emission geometry found in Mohan et al (2019a) and Mohan (2021). Future studies with simultaneous observations with the Solar Orbiter and sensitive radio interferometers will be able to investigate possible relationships between these two phenomena in detail.…”
Section: Possible Relationship With Campfiressupporting
confidence: 62%
See 1 more Smart Citation
“…Quasiperiodic oscillation in the radio lightcurve was seen from the sun in which the period was associated with the timescale in which magnetic stress is built up and then relieved through reconnection (e.g. Mohan et al 2019).…”
Section: Non-persistent Enhancements Observed From Cu Virmentioning
confidence: 99%
“…These observations cannot be explained in terms of the conventional Alfvènic oscillations. In the same data set, Mohan et al (2019a) also find an unrelated weak flare seen in the EUV and soft X-rays. Their analysis shows that this flare was responsible for some local coronal heating.…”
Section: Solar Heliospheric and Ionospheric Sciencementioning
confidence: 67%